The genesis and development of deep convective storms - Sinclair, P. C., author; Purdom, J. F. W., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1983)
During the summer of 1980, NESS sponsored a research aircraft field program that combined research aircraft flights with rapid scan GOES imagery. The purpose of the research program was to provide a better understanding of the natural mechanisms that lead to the development of deep convective storms through integration and analysis of those special data sets. Data were taken during the field program with the goal of providing an in-depth understanding of the fundamental mechanism - arc cloud line interactions - that lead to the development of deep convection. The experiment provided a unique data base from which the convective storm's mesoscale flow field (dynamic and thermodynamic properties) could be documented by in-situ measurements and near simultaneous GOES visible and infrared data. Several arc clouds were penetrated on three separate GOES rapid scan imaging days, and representative results from those penetrations are given in the text. It is hoped that the improvement in knowledge gained from this experiment will lead to a better understanding of mesoscale dynamics, which is of great importance for the development of improved short-range forecasting techniques.
January 1983.
Keywords: Storms; Clouds; Convection (Meteorology)